2022
DOI: 10.18103/mra.v10i10.3125
|View full text |Cite
|
Sign up to set email alerts
|

Palestinian Healthcare Workers Mental Health Challenges during COVID-19 Pandemic: A Cross-Sectional Study

Abstract: Healthcare workers have been working on the frontlines since the COVID-19 pandemic in 2019. In Palestine Healthcare workers have been experiencing compounded stress given their preexisting limited access and resources as imposed by the Israeli colonial system and their management of the novel coronavirus. This study aimed to investigate the impact of COVID-19 on Palestinian healthcare workers’ mental health in relationship to various demographic variables that have been found to correlate to expressed distress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…This stress is increased due to their pre-existing limited access and resources, imposed by the colonial system, and their management of the new coronavirus, in certain vulnerable subgroups (health care workers) who are likely to require psychological interventions). Indeed significant associations were observed between attitude toward interprofessional teamwork, gender, marital status, occupation, work experience, current work location (clinics), spiritual influences, perceived competence, difficulties in daily life, income level, confidence in individual instincts, level of control over aspects of resilience, provision of COVID-19 patient care, history of COVID-19 testing, history of COVID-19 testing or infection, and availability of mental health support in the workplace ( 7 , 8 , 14 , 16 , 19 , 24 28 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This stress is increased due to their pre-existing limited access and resources, imposed by the colonial system, and their management of the new coronavirus, in certain vulnerable subgroups (health care workers) who are likely to require psychological interventions). Indeed significant associations were observed between attitude toward interprofessional teamwork, gender, marital status, occupation, work experience, current work location (clinics), spiritual influences, perceived competence, difficulties in daily life, income level, confidence in individual instincts, level of control over aspects of resilience, provision of COVID-19 patient care, history of COVID-19 testing, history of COVID-19 testing or infection, and availability of mental health support in the workplace ( 7 , 8 , 14 , 16 , 19 , 24 28 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…The pandemic of coronavirus (COVID-19) has a social and psychological impact on the mental health of health workers worldwide (1)(2)(3)(4)(5)(6)(7)(8). However, few studies have been conducted in developing countries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study further showed a statistically significant finding that the prevalence of COVID-19 infection was twice as much higher during the pre-vaccination period compared to that of the post-vaccination period (χ 2 = 41.446, p < 0.001). However, it is in contrast to other reports which showed a rise in the prevalence of SARS-CoV-2 infection among HCWs in the period following the introduction of COVID-19 vaccines compared to the prevaccination period attributed partly to the decrease in vaccine effectiveness to emerging variants of SARS-CoV-2 [17] Other attributable factors have to do with the significant increase in the incidence of COVID-19 around the world leading to issue of mental and psychological disturbances from long working hours resulting in lowered resilience, burnout, low quality of life (QoL) among HCWs, experiences of depressive and anxiety symptoms, with females, physicians, and less experienced Healthcare workers showing elevated levels of symptomology [18][19][20][21][22][23][24], The prevalence of COVID-19 infection among HCWs following the introduction of vaccines was low and comparable to a global estimate [25] This decline may be attributed to the success of the COVID-19 vaccination programme buttressing the effectiveness of the vaccine against infection with SAR-CoV-2 and probably combined with the improvement in the IPC measures adopted by HCWs across the state [26,27].…”
Section: Discussionmentioning
confidence: 99%